The Influence of Financial Statements on Investment Decision-Making at Bank Neo Commerce Based on the 2023 Financial Report - Yanuar Ramadhan; Novi Afriyani Ramdani; Clarissa Tjandra; Siti Muallifah; Roviuddin Roviuddin (Eduvest - Journal of Universal Studies, 2025)
This study analyzes the financial statements of Bank Neo Commerce for the year 2023 to evaluate financial performance and its impact on management and investment decisions. Data were obtained from the annual financial statements, including the balance sheet, income statement, cash flow statement, and statement of changes in equity. The analysis focused on liquidity, solvency, and profitability ratios to assess the bank's financial health and operational efficiency. The results indicate that Bank Neo Commerce experienced a 20% increase in total assets from IDR 8.3 trillion to IDR 10 trillion, with annual revenue reaching IDR 900 billion and a net loss of IDR 515 billion. The liquidity ratio was at a healthy level of 1.4, while the solvency ratio of 0.4 indicates moderate use of debt relative to equity. The profitability ratio remained stable at 16.7%, reflecting the bank's ability to maintain strong profit margins despite competitive market conditions. The study also evaluated the impact of digitalization strategies and product innovation on financial performance. Bank Neo Commerce successfully attracted new customer segments and improved operational efficiency through the implementation of digital technology and app-based banking services. The implications of these findings suggest that effective digitalization strategies can enhance the bank's competitiveness and overall financial performance. In conclusion, the 2023 financial statements of Bank Neo Commerce indicate solid performance with positive growth prospects. These findings are expected to serve as a reference for the bank's management in strategic decision-making and for investors in assessing investment potential.